2014
DOI: 10.1080/15459624.2013.877591
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Face Shields Against Cough Aerosol Droplets from a Cough Simulator

Abstract: Health care workers are exposed to potentially infectious airborne particles while providing routine care to coughing patients. However, much is not understood about the behavior of these aerosols and the risks they pose. We used a coughing patient simulator and a breathing worker simulator to investigate the exposure of health care workers to cough aerosol droplets, and to examine the efficacy of face shields in reducing this exposure. Our results showed that 0.9% of the initial burst of aerosol from a cough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
211
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(226 citation statements)
references
References 20 publications
3
211
0
5
Order By: Relevance
“…[12] However, as highlighted in a recent Institute of Medicine report, [15] little is known about the effectiveness of face shields in preventing the transmission of viral respiratory diseases. Utilizing a cough aerosol simulator loaded with influenza virus (aerosol volume mean diameter of 8.5 µm) and a breathing simulator, Lindsley et al [16] reported 96% and 92% reductions in the risk of inhalational exposure immediately after a cough for a face shield at distances of 18 in (46 cm) and 72 in (183 cm), respectively. Decreasing the aerosol size to 3.4 µm resulted in the face shield blocking 68% of the inhalational exposure at 18 in (46 cm) immediately after the cough and 23% over 1-30 min post-cough (during which time the larger aerosol particles had settled out and droplet nuclei had formed and remained airborne so that flow occurred more easily around the edges of the face shield).…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] However, as highlighted in a recent Institute of Medicine report, [15] little is known about the effectiveness of face shields in preventing the transmission of viral respiratory diseases. Utilizing a cough aerosol simulator loaded with influenza virus (aerosol volume mean diameter of 8.5 µm) and a breathing simulator, Lindsley et al [16] reported 96% and 92% reductions in the risk of inhalational exposure immediately after a cough for a face shield at distances of 18 in (46 cm) and 72 in (183 cm), respectively. Decreasing the aerosol size to 3.4 µm resulted in the face shield blocking 68% of the inhalational exposure at 18 in (46 cm) immediately after the cough and 23% over 1-30 min post-cough (during which time the larger aerosol particles had settled out and droplet nuclei had formed and remained airborne so that flow occurred more easily around the edges of the face shield).…”
Section: Researchmentioning
confidence: 99%
“…Decreasing the aerosol size to 3.4 µm resulted in the face shield blocking 68% of the inhalational exposure at 18 in (46 cm) immediately after the cough and 23% over 1-30 min post-cough (during which time the larger aerosol particles had settled out and droplet nuclei had formed and remained airborne so that flow occurred more easily around the edges of the face shield). [16] Shoham et al [17] sprayed a fluorescent dye (particle diameter ∼5µm) at a distance of 20 in (50 cm) away from a mannequin head outfitted with various types of PPE. They found that a face shield with head/neck length, three separate contact points at the forehead, and side curve reaching to the point of the ear (Bettershield TM , Southmedic, Barrie, Ontario, CA), or the combination of this face shield and an N95 filtering facepiece respirator (N95 FFR), protected the eyes, nares and mouth from contamination.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand hygiene Fraction of virus remaining on hands after hand hygiene 0.05 (18,19) 40% (16,(20)(21)(22) Eye protection Fraction of virus that bypasses the goggles or face shield 0.04 (23) 50% Facemask Fraction of sprayed and contact-transferred virus that penetrates or bypasses facemask 0.10 b (24,25) 50% b (16,17,(25)(26)(27) Percent reduction in frequency of contact with the facial portals 90% (28) N95 filtering facepiece respirator Fraction of sprayed and contact-transferred virus that penetrates through respirator 0.05 b 20% b (16,17,(25)(26)(27) Protection factor d Uniform: range 5-10 (29,30) Percent reduction in frequency of contact with the facial portals 90% (28) Isolation Fraction reduction in the duration of occupational exposure 0.18 (7) 80% (31)(32)(33)(34) Percent increase in compliance with hand hygiene, eye protection, facemasks or respirators, and full compliance with gloves 25% (7,32,35,36) Surface decontamination Fraction of virus remaining on surfaces 0.05 (37,38) 50% e The protection factor is a ratio of the concentration of particles outside the respirator to that inside. The assigned protection factor of these respirators is 10 (30) , but lower performance was considered due to issues with long-term fit and use practices.…”
Section: Resultsmentioning
confidence: 99%
“…N95 respirator or PAPR) [33,38,39]. Use of a face shield rather than glasses/goggles also has been shown to reduce contamination of respirators by particles but only 59% of ME/C respondents routinely wear them [40].…”
Section: Discussionmentioning
confidence: 99%